Identifying Preferences under Risk from Discrete Choices - Chiappori, Pierre-André; Gandhi, Amit; Salanié, Bernard; Salanié, Francois (American Economic Review, 2009)
Identifying Preferences under Risk from Discrete Choices by Pierre-Andre Chiappori, Amit Gandhi, Bernard Salanie and Francois Salanie. Published in volume 99, issue 2, pages 356-62 of American Economic Review, May 2009